Avaliação da potência do hormônio da paratireóide humano recombinante por bioensaio, métodos cromatográficos e eletroforético - Maldaner, Fernanda Pavani Stamm (2017)
The human parathyroid hormone (hPTH) is a polypeptide secreted by the parathyroid glands that is essential for the maintenance of the calcium ion homeostasis in the blood. The recombinant DNA technology has enabled the expression of hPTH gene in Escherichia coli, and thus the large-scale production of recombinant human parathyroid hormone (rhPTH 1-34), teriparatide, which contain the active amino-terminal fragment of the full length hPTH. The rhPTH is clinically used to treat osteoporosis at high risk of fractures in postmenopausal women, men with osteoporosis primary or hypogonadal and adults with glucocorticoid-induced osteoporosis (GIO). Cappilary zone electrophoresis (CZE) method was developed and validated for the assessment of rhPTH in biopharmaceutical formulations. The analysis for CZE method was performed on a fused-silica capillary (effective length, 40 cm; 50 μm i.d.), using electrolyte solution consisted of 50 mM dihydrogen phosphate solution at pH 3.0. The capillary was maintained at 25º C, the applied voltage was 20 kV. Injections were performed using a pressure mode at 50 mbar for 45 s, with detection by photodiode array detector set at 200 nm. Separation was obtained with a migration time of 5.3 min, and was linear over the concentration range of 0.25-250 μg mL-1 (r2 = 0.9992). The limits of detection and quantitation were 0.12 and 0.40 μg/mL, respectively. Specificity and stability-indicating capability were established in degradation studies, which also showed that there was no interference of the excipients. The accuracy was 100.28% with bias lower than 0.85%. Moreover, the in vitro cytotoxicity test of acidic, photolytic and thermal degradated forms showed significant differences (p<0.05) compared to intact molecule. The cell proliferation and alkaline phosphatase activity bioassays in UMR-106 cells were developed and applied to assess the biological activity of rhPTH in biopharmaceutical formulations The results of content/potency were correlated to those of the validated reversed-phase liquid chromatography (RP-LC), size-exclusion liquid chromatography (SE-LC) and CZE methods, showing significant correlation (p> 0.05) Thus, the application of the validated physico-chemical methods together with in vitro bioassays, was suggested to improve quality control of rhPTH biotechnology-derived product and to support studies of biosimilars.